English as Lingua Franca - Gasparyan, Seda (Armenian Folia Anglistika, 2015)
The article highlights English as Lingua Franca and emphasizes the importance of teaching Language for Special Purposes (LSP). The content of the notion “lingua-franca” is analysed on the basis of a number of linguistic works devoted to the English language status. English as Lingua Franca refers to the use of English as a medium of communication between speakers of different languages. Nowadays, contacts between people with different cultural backgrounds are becoming more frequent and much closer. Highly developed skills in intercultural communication have a significant bearing on the quality of relationships between people of various nationalities and cultures. In recent years ELF has been studied by many linguists interested in how its pronunciation, vocabulary and grammar are different from other varieties of English. ELF has now established itself as a major and expanding field of academic research. Its interconnections with teaching and other disciplines are being currently discussed, acknowledged and investigated.
Keywords: Lingua Franca (ELF); Language for Special Purposes (LSP); General English; scientific communication; language acquisition